Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Simulasi Interaktif Terhadap Keterampilan Generik Sains Siswa SMA Pada Materi Elastisitas - Fahmi Yahya; Syarif Fitriyanto (Department of Physics Education, Universitas Mataram, 2016)
The aim of this study is to examine the effects of problem based learning model assist with interactive simulation to science generic skill of students. This is an experimental research with pretest-posttest control group design. Data were collected by using generic skill achievement test and analyzed by using mean-difference test and calculating normalized gain scores. Research finding showed that there is significance difference between experimental group and control group. Moreover, mean value for the experimental group is higher than control group. Problem based learning model assist with interactive simulation is better in improving student science generic skill than without interactive simulation.